Prevalence and characteristics of scoliosis among ethiopian schoolchildren aged 6–15 Years: A school-based cross-sectional study - Reta Wakoya; Mekbeb Afework; Alemayehu Worku; Firaol Dandena; Stefano Bolongaro; Timothy Nunn (PLoS ONE, 2026)
Background Scoliosis is a progressive spinal deformity that often develops during childhood and adolescence. In Ethiopia, population-level prevalence data are scarce, and school-based screening, though practical, may overestimate cases without radiographic confirmation. Understanding its distribution and severity is critical for guiding clinical and public health strategies. Objectives To estimate the prevalence of scoliosis among Ethiopian schoolchildren, characterize its types and severity, and examine associations with clinical and anthropometric variables. Methods A cross-sectional school-based screening was conducted from March 2024 to June 2025 across 42 public primary schools in six regions. Children aged 6–15 years were screened using the Adam’s Forward Bend Test and scoliometer; suspected cases (ATR ≥ 7°) were referred for radiographic confirmation. Prevalence estimates and associations were analyzed using chi-square tests and t-tests. Data were analyzed in Python, with quality control ensured through standardized training, pilot testing, and double-entry verification. Results Of 32,000 children screened, 48 were suspected of scoliosis (0.15%; 95% CI: 0.11–0.20%), and 21 were radiographically confirmed (0.066%; 95% CI: 0.04–0.10%). Congenital scoliosis was most common (61.9%), with male predominance (69%), while idiopathic scoliosis (23.8%) was more frequent in females (60%). Neuromuscular and syndromic scoliosis were rare. Severity analysis showed male predominance in mild and very severe cases, with equal sex distribution in severe scoliosis. The mean Cobb angle was 47.4° (SD ± 28.9), most cases involved the thoracic spine (52.4%), and the rib hump was typically right-sided (61.9%). Cobb angle correlated positively with ATR (r = 0.61) and thoracic loss (r = 0.48), and negatively with age (r = –0.24) and thoracic height (r = –0.46). Conclusion This study shows that scoliosis prevalence within the school population is low, with adolescent idiopathic cases markedly underrepresented compared to other school-based screening reports. These findings suggest that nationwide school screening programs are not recommended. Instead, efforts should prioritize strengthening diagnostic and referral pathways for clinically evident cases to ensure timely access to specialized care.